Prevalence of stigma towards mental illness among Portuguese healthcare professionals: a descriptive and comparative study - Torres, Inês N.; Pereira, Helena P.; Moreira, Maria Beatriz P.; Marina, Sílvia; Ricou, Miguel (Frontiers in Psychiatry, 2024)
Background: Stigmatising attitudes among healthcare professionals can hinder access to healthcare, making it important to address this issue. This study aimed to investigate the prevalence of stigma related to mental illness among Portuguese healthcare professionals and to compare the results among mental health professionals, General Practitioners (GPs) and other health professionals.Methods: An online cross-sectional observational study was conducted in Portugal using Google Forms® to collect data. The data collection process lasted five months, from September 2023 to January 2024. Participants were recruited from various professional associations and Health Centre Groups, through a purposive sampling. The study used the Portuguese version of the Opening Minds Stigma Scale for Healthcare Providers (OMS-HC) to measure stigma which assesses three dimensions: attitudes towards disclosure and help-seeking, attitudes towards people with mental illness, and attitudes towards social distance.Results: A total of 292 healthcare professionals participated in the study. In Portugal, healthcare professionals displayed low to moderate levels of stigma towards mental illness (M = 22.17, SD = 5.41).Mental health professionals demonstrated significantly lower levels of stigma (M=20.37, SD=5.37) compared to other healthcare professionals (M=24.15, SD=4.71), including GPs (M=23.97, SD=5.03).Additionally, having a close friend or relative with mental illness seemed to be related with lower levels of stigma for the dimension attitudes towards social distance (M=6.93, SD=2.50), compared to not having one (M=7.60, SD=2.56). On the other hand, a personal history of mental illness indicated higher levels of stigma for the dimension disclosure and help-seeking (M=8.95, SD=3.07), compared to having no history of mental illness (M=8.16, SD=2.67).Conclusion: This study indicates that Portuguese healthcare professionals have stigmatising attitudes towards mental illness, although at low to moderate levels. Training and frequent interaction with people with mental illness seem to be associated with lower levels of stigma. Personal experience of mental illness seems to follow the opposite path regarding disclosure and seeking help. Thus, further research is necessary to evaluate the effectiveness of anti-stigma measures and deepen the study of the concept of self-stigma in healthcare professionals.